The Mechanism of Ensuring the Sustainability of The Development of The Higher Education System During the Formation of a New Technological Order - Glushchenko, Valery Vladimirovich (Bumi Publikasi Nusantara, 2023)
The subject of the article is the study of the mechanism of ensuring the sustainable development of the higher education system in the process of formation of a new technological order. The object of the article is the higher education system. The purpose of the work is to ensure the sustainable development of the higher education system during the formation of a new technological order. To achieve this goal, the following tasks of this study are solved: research and clarification of the concept of sustainable development of the system of higher education, description of the sources of the risk of loss of stability in the process of development of the higher education system associated with the transition to a new technological order, and study of the elements of the mechanism for ensuring sustainable development of the higher education system. The scientific novelty of this article is to determine the description of the mechanism for ensuring the sustainable development of the higher education system and its constituent elements.